Dilthey's Dream Essays on human nature and culture - Freeman, Derek (ANU Press, 2017)
With great eloquence, Derek Freeman takes the reader on an intellectual journey through the complexities of philosophical anthropology. Even while the controversial Nature-Nurture debate raged, Freeman contended that the crucial fact that humans had the capacity to make choices was 'both intrinsic to our biology and basic to the very formation of cultures'. Thus the scene was set for his widely publicised criticism of Margaret Mead's book Coming of Age in Samoa. Publishing her research in 1926, Mead concluded that all human behaviour was the result of social conditioning. Freeman refuted this assumption in 1983, urging closer interactions between the biological sciences and cultural studies to bridge the ever-widening chasm threatening all studies of humankind. Dilthey's Dream is an engagingly powerful set of essays depicting the depth of one man's thinking on issues, which consumed a lifetime.